Synthesis of dimethyl ether – environmentally friendly diesel fuel (Eurasian Journal of Ecology, 2016)
Investigated the reaction of dimethyl ether from methanol to obtain a flow apparatus at atmospheric pressure, for the first time during the production of dimethyl ether as a carrier for catalysts used modular metal carrierswith high emissivity and low gas dynamic resistance.
Keywords: Catalyst; methane; dimethyl ether; methanol; natural gas; the carrier.